"We are worse off, many of us are trying to survive": Stories of expulsions and extractivism in Argentina - Castilla, Malena Ines (2023)
In Argentina, extractive activities, land grabbing and territorial transformation have led to the expulsion of part of the population. These transformations have led to changes in the ways of living and producing these landscapes, as well as changes in the environment and climate. As a result, some international and national organizations have chosen to define the people affected and expelled from these territories as 'environmental migrants and/or climate displaced persons'. Through the systematization and analysis of different documentary sources -obtained from our fieldwork and interviews, but also from the study of statistics, agricultural and population censuses, maps, technical reports, journalistic notes, etc.- we propose to conceptualize these mobilities as a result of the advance of extractive frontiers over the territories and the expulsion -generally violent- of their inhabitants, mainly indigenous populations. We also seek to describe the trajectories that forced these actors to migrate and the conditions of habitability in which they had to settle, deepening existing inequalities and violations. This work is as a proposal to address the problem referred to here, which is not currently part of the Argentinean government's agenda and, therefore, no policies are planned to mitigate the consequences and emerging conflicts.